2015
DOI: 10.1007/s13762-014-0740-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for synthesis of nano-γ-Al2O3: study of adsorption behavior of chromium, nickel, cadmium and lead ions

Abstract: Nano-c-Al 2 O 3 adsorbent was synthesized by the novel sol-gel method. The adsorbent was characterized by transmission electron microscope, Fourier transform infrared and X-ray powder diffraction. The effects of several variables such as, adsorbent weight, pH and contact time on adsorption of chromium (Cr 6? ), nickel (Ni 2? ), cadmium (Cd 2? ) and lead (Pb 2? ) ions were studied in batch experiments. The results showed that the synthesized nano-c-Al 2 O 3 had a good capacity to adsorb Cr and Pb. The kinetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In addition to the above heavy metals, Al 2 O 3 nanomaterials have also been reported to remove Hg (II), As (III), Cu (II), Ni (II), Cr (VI), etc. and have exhibited decent removal capabilities towards these elements [196,197,198,199].…”
Section: Nanomaterials For Removing Heavy Metalsmentioning
confidence: 99%
“…In addition to the above heavy metals, Al 2 O 3 nanomaterials have also been reported to remove Hg (II), As (III), Cu (II), Ni (II), Cr (VI), etc. and have exhibited decent removal capabilities towards these elements [196,197,198,199].…”
Section: Nanomaterials For Removing Heavy Metalsmentioning
confidence: 99%
“…46 Mahapatra et al(2013) prepared iron oxide-alumina mixed nanocomposite fiber using electrospinning method and its sorption nature was studied towards Cu 2+ , Pb 2+ , Ni 2+ and Hg 2+ and the % removal was found to be in order: Hg 2+ >Ni 2+ > Pb 2+ >Cu 2+ with adsorption capacities 63.69 mg/g, 32.36 mg/g, 23.75 mg/g and 4.98 mg/g respectively. 47 Shokati Poursani et al (2015) prepared nano-γAl2O3 by precipitating hydrated Aluminum hydroxide by mixing 1,2-epoxybutane with an alcoholic solution of AlCl3.6H2O and then diluting with water and subsequently, heating the precipitate to high elevated temperatures and then grinded 20 . The prepared nano-γ-Al2O3 was investigated for its sorption nature towards the cations: Cr 3+ , Cd 2+ , Ni 2+ and Pb 2+ and NANO ALUMINUM OXIDES AS ADSORBENTS K. Ravindhranath and M.Ramamoorty found that the sorption followed the order: Cr 3+ > Cd 2+ >, Ni 2+ > Pb 2+ with the sorption capacities respectively 13.3 mg/g, 6 mg/g, 1.1 mg/g and 0.33 mg/g (at temp 25 o C).…”
Section: Removal Of Metal Ionmentioning
confidence: 99%
“…One of the reasons for the broader application of nanoadsorbent is the greater surface area to volume ratio, the reactivity, and the ability to absorb higher contamination relative to the macro and micro scales of the same substance. The lignin-containing cellulose nanofibrils (LCNFs) consists of lignin and hemicellulose, one of the thinnest and newest fibers in the world with attractive features such as renewability, non-toxicity, reasonable cost, and high specific resistance (8,9).…”
Section: Introductionmentioning
confidence: 99%